-343=-7(1+6v)

Simple and best practice solution for -343=-7(1+6v) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -343=-7(1+6v) equation:


Simplifying
-343 = -7(1 + 6v)
-343 = (1 * -7 + 6v * -7)
-343 = (-7 + -42v)

Solving
-343 = -7 + -42v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '42v' to each side of the equation.
-343 + 42v = -7 + -42v + 42v

Combine like terms: -42v + 42v = 0
-343 + 42v = -7 + 0
-343 + 42v = -7

Add '343' to each side of the equation.
-343 + 343 + 42v = -7 + 343

Combine like terms: -343 + 343 = 0
0 + 42v = -7 + 343
42v = -7 + 343

Combine like terms: -7 + 343 = 336
42v = 336

Divide each side by '42'.
v = 8

Simplifying
v = 8

See similar equations:

| (8k+7)(k+1)=9 | | (2)-(-b)=6 | | 118=-8+7(8-2x) | | (-8)+x=-3 | | 2w^2+3w=324 | | P(p-3)-6p-18=0 | | 7y(3x+2y)= | | 8/14x=6/10 | | 8/14=6/10 | | 28y-187=15x | | 5/9x=60 | | 7p^2-12p-2=5p-8 | | -2x+8=3x+10 | | 63=6n+3n-2n | | 15y+187=28x | | 6h^2+26h-2=-10 | | 0.36*(11/2) | | x^5+540=0 | | 2.5x+2.8=-1.2x+9.8 | | F(x)=8-2x-x^2 | | (x+6)=2(1-x) | | 2.3x+2.8=-1.3x+9.8 | | 4m+5m-9=3m+m+6 | | 6k^2+k-12=0 | | 4x-3/5x÷4x^2-5/5 | | x^5-x^4-x^3+x^2-2x+2=0 | | 2.5x=11+3x | | X^2-9x-56=0 | | r/2-r/3=3 | | cot^2(x)=3 | | 25/4=R/5 | | 4y^2=400 |

Equations solver categories